PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI KARYAWAN TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Hotel Resty Menara Pekanbaru) - Mega Astuti; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study was conducted at Resty Menara Pekanbaru Hotel wher located on Sisingamangaraja, No. 102, Pekanbaru. The problem in study in the not achieving organizational goals in the last five years, this is allegedly influenced by employee performance. This study aims to determine the influenced of organizational culture and competence employee on employee performance (Case study at the Resty Menara Pekanbaru Hotel).This study is using descriptive and quantitative analysis with the help of SPSS program. The target population compirised of 51 employees in Resty Menara Pekanbaru Hotel. The sampling chosen is based on census method and saturated sample that 51 person that taken from overall target polulation. The method of data collection is done by distributing questionmaires. To test the hypothesis in this study is using simple linear analysus and analysis of multiple linear.The result of research indicates that for the t test, organizational culture and competence employee partially have a significant effect on employee performance. And the result of F test indicates that organizational culture and competence employee simultaneously have a significant effect on employee performance (Case study at the Resty Menara Pekanbaru), with an R Square value of 0, 719. This shows that the organizational culture and competence employee have an influence of 71, 9% of the performance of employees with Pretty Good categorization, while the remaining 28, 1% is influenced by other variables not included in this study.Keywords : Organizational Culture, Competence Employee, Employee Performance